The Concept of Islamic Education Management from the Perspective of the Qur'an and Al-Hadith - Riinawati Riinawati (Tafkir: Interdisciplinary Journal of Islamic Education, 2022)
This article aims to determine the concepts of Islamic education management concepts of the Al-Quran and Al-Hadis perspectives. The research method for this scientific article is to use the library research method. The results of this study are that Islamic education management is an activity to mobilize and integrate all Islamic education resources in order to achieve the goals of Islamic education that have been set previously. The resources that are mobilized and combined to achieve these educational goals of the course include the so-called 3 M (human, money, and material), and all of them are not only limited to schools/madrasahs or leaders of Islamic universities. The conclusion of this research is in Islamic Education Management, but planning is also the main key to determining the next activity. Without careful planning, other activities will not run well and can even fail. Therefore, plan as carefully as possible in order to achieve satisfactory success.